Chinese porcelains and the decorations of Omani mihrabs - Goffriller, Martin S.; Hongjiao, Ma; Bandyopadhyay, Soumyen; Henderson, Julian (Proceedings of the Seminar for Arabian Studies, 2015)
This paper explores the history of the Chinese porcelain trade in Oman with the aim of gauging the impact of these wares on Oman's religious architecture. The large quantities of porcelain surface finds from the interior and the comparatively unusual reliance on them for the decoration of prayer niches, in the presence of equally valuable wares from Persia and elsewhere, suggest an elevated status for these objects, which is not necessarily a product of their immediate monetary value. Chemical and stylistic analyses were carried out to determine the dates and provenance of the ceramics studied, with the aim of gaining a better understanding of their introduction into the Omani market and their relation to religious design schemes.